Inflammatory and immunological markers in preterm infants: correlation with disease - JURGES, E S (Blackwell Science Inc, 1996)
Newborn infants often suffer from bacterial and viral infections without presenting typical symptoms. Therefore, reliable methods for detecting and monitoring sepsis in the newborn would be beneficial. In older patients C-reactive protein (CRP) and neopterin have proved useful serum markers of infection and inflammation. Both of these markers are regulated by cytokines, and it has been proposed that cytokines themselves could be used to monitor immune activation and infection. This study has examined the levels of CRP, neopterin, soluble IL-2R, tumour necrosis factor-alpha (TNF-α) and interferon-gamma (IFN-γ) in cord blood samples from both pre-mature and term neonates. Having established reference ranges for these analytes, serial measurements were made in babies requiring intensive care support. The results suggest that in preterm infants the simultaneous measurement of CRP and neopterin, and possibly soluble IL-2R, may provide an accurate early diagnosis of sepsis and may be of use in differentiating between bacterial and viral etiologies. In addition, serial measurement of these markers may help in the early diagnosis of necrotizing enterocolitis (NEC).